Developments in research on the relationship between oral-gut microbes and respiratory diseases - XIANG Huanhuan, DAI Zhouli, ZHANG Yufei, WU Jiawen, HAN Zihui, CHEN Siyi (Kouqiang yixue)
The imbalance of microbiota is related to various diseases in the human body, and the gut, as the largest microbial habitat in the human body, is closely related to the oral microbial environment. The oral microbiota can migrate to the intestinal mucosa with the digestive system. At the same time, microbial transmission from the gut to the mouth can also occur through interpersonal and community transmission. Microbial transmission between the mouth and intestines can shape or reshape the microbial ecosystem in the two habitats, ultimately regulating the pathogenesis of the disease. The dysbiosis of the oral-gut microbiota axis can have a significant impact on related diseases such as respiratory diseases. This article reviews the research status of the relationship between oral-gut microbes and respiratory diseases.